The Use of Infographics, Tables and Graphs in the Hospitals and Health Services Quality Account in Australia - Abdel K Halabi; Lee Brown (ACHSM, 2022)
Objective: This study will investigate whether removing the Quality Accounts purpose and aim led to differences in the number of Infographics, Tables and Graphs used over four years. Design: A content analysis was performed on the Quality Accounts of six Hospitals and Health Services from 2016 to 2019. Statistical analysis was then performed to examine differences in the use of Infographics, Tables and Graphs in the Quality Account Setting: The six Hospitals and Health Services were operating in a rural geographical area in the state of Victoria, Australia. Results: Even though some significant differences were found , this was largely due to yearly variability in the use of Infographics, Tables and Graphs. The six Hospitals were quite different in their Quality Account presentations because these reports are structured to a particular community. Conclusions: The removal of the purpose and aim has not affected the number of Infographics, Tables and Graphs. While limitations are noted, a number of future research opportunities stem from this study to enhance the Quality Account and overall understandability of Hospital reports.